Parallel Inductive Logic Programming System for Superlinear Speedup - Nishiyama, Hiroyuki; Ohwada, Hayato (Inductive Logic Programming, 2018)
In this study, we improve our parallel inductive logic programming (ILP) system to enable superlinear speedup. This improvement redesigns several features of our ILP learning system and parallel mechanism. The redesigned ILP learning system searches and gathers all rules that have the same evaluation. The redesigned parallel mechanism adds a communication protocol for sharing the evaluation of the identified rules, thereby realizing superlinear speedup.